Handling Corruption as a Social System: An AGIL-Based Socio-Legal Analysis of Prosecutorial Practices in South Sulawesi - Muhammad Djaelani Prasetya (Law Research Review Quarterly, 2025)
This article examines the handling of corruption in South Sulawesi through a socio-legal approach by applying Talcott Parsons' AGIL (Adaptation, Goal Achievement, Integration, and Latency) framework to structured interviews. Different from the dominant approach that frames the handling of corruption primarily in terms of legal compliance, institutional capacity, or political matters, this article conceptualizes handling as a dynamic social system shaped by the institutional practice and professional experience of prosecutors. Empirical data was collected through structured interviews with 25 prosecutors from 24 district attorney's offices and 1 person from the South Sulawesi High Prosecutor's Office, all of whom had first-hand experience in dealing with corruption. The findings suggest that the handling depends on a functional balance between technical adaptation to complex corruption schemes, the achievement of substantive objectives oriented towards the deterrent effect and recovery of assets, institutional integration through teamwork and inter-agency coordination, and latency mechanisms that support professional values, and psychological stability. Disruption to AGIL's function can weaken the performance of handling corruption. This article offers a contribution by developing the AGIL framework from the normative side to the practical direction of institutional-based. This article affirms the concept of institutional balance to explain the legal structure, organizational coordination, and professionalism interacting in maintaining the handling of corruption at the regional level.